Роговые накладки лука Карпатской котловины X-XI вв - Биро, А.; Ланго, П.; Тюрк, А. (Степи Европы в эпоху средневековья, 2009)
The authors have carried out the functional determination and specification of antler overlays found in burial 6 during the authentic excavations of the 10th c. cemetery located at Szentes, Derekegyhazi-oldal. An overlay that formed a back of a bow-grip is extremely rare in the material culture of the Carpathian Basin of the 10th-11th cc. Moreover, only five overlays similar to those found at the Szentes cemetery are known by now. Therefore, identification of their accurate chronological position in the above mentioned period is impossible In the second part of the paper the authors determined the Eastern European parallels of the bow-grip overlays of the Carpathian Basin collect, stating that similar bow-grip overlays were common to the east of the Carpathian Basin in the whole Eurasian region in the 8th-11th cc. Accurate formal counterparts of the bow-grip overlays of the Carpathian basin of the 10th-11th cc within Eastern Europe and the 10th c. are to be found in the material culture of Sarkel (Belaia Vezha) and the surrounding regions, although they are known even in the areas to the east of the Volga river, for example in Altai region.